EVALUATION OF STORAGE LENGTH ON THE NUTRIENT QUALITY OF WIN PROB FERMENTED WOODS (OTW_PRO) IN LIQUID FORM - Vicky Aditya Pratama; Dini Julia Sari Siregar (Journal of Innovation Research and Knowledge, 2024)
The aim of this research is to find out how long the best storage time for the fermentation process is on the quality of Win Prob (otw_pro) fermented onggok nutrients in liquid form. The hypothesis of this research is to find out how long the best storage time for the fermentation process is on the quality of Win Prob (otw_pro) fermented onggok nutrients in liquid form. The materials used in the research were onggok, Win Prob and molasses. Materials for chemical feed nutrition tests are H2SO4, NaOH, acetone, boric acid HCl and methyl red indicator. The tools used are plastic jars, buckets, knives and scales. The tools used in nutritional chemistry tests are calorie meter bombs, thermometers, digestion tools, distillation tools, titration tools, and shoxlet tools. The research method used in the research was a non-factorial Completely Randomized Design (CRD) with 5 treatments and 4 replications. The treatments given were as follows: FP0: storage time 0 days (control), FP1: storage time 1 week, FP2: storage time 2 weeks, FP3: storage time 3 weeks and FP4: storage time 4 weeks. The parameters observed include analysis of the nutritional content of crude protein, crude fiber and gross energy. Proximate testing is carried out in the laboratory. The conclusion of this research is that onggok fermented with Win Prob probiotics in liquid form with a storage period of 4 weeks is the best treatment which can increase crude protein, gross energy and reduce crude fiber